Optogenetic vagal nerve stimulation attenuates heart failure by limiting the generation of monocyte-derived inflammatory CCRL2+ macrophages - Li, Guoqi; Zhang, Congcong; Li, Yang; Yang, Jie; Wu, Jianing; Shao, Yihui; Ma, Ke; Zhang, Xinyu; Zhu, Shuolin; Du, Jie; Ma, Xin-Liang; Wang, Liping; et al. (Immunity, 2025)
Parasympathetic neuronal dysfunction is associated with heart failure (HF), yet the underlying mechanism is poorly understood. Here, we report that targeted vagal nerve stimulation (VNS) using optogenetics attenuated cardiac remodeling and HF induced by pressure overload. Unbiased approaches revealed that VNS decreased the proportion of Ccrl2+ macrophages, which were derived from myeloid monocytes and exhibited a distinct tumor necrosis factor alpha (TNF-α) cytokine-responsive, pro-hypertrophic, and profibrotic signature. Elimination of Ccrl2+ macrophages prevented cardiac remodeling and HF. Ccrl2+-macrophage-specific overexpression or global genetic loss of α7 nicotinic acetylcholine receptor (α7nAChR) highlighted their crucial contribution to VNS-mediated cardioprotection. Activation of α7nAChR inhibited Ccrl2+ macrophages' TNF-α responsiveness through increased expression of the transcription factor NRF2. Cardiac Ccrl2+ macrophages and TNF-α-responsive proteins positively correlated with cardiac remodeling and dysfunction in humans. An α7nAChR agonist effectively blocked the development of HF. These results suggest that the vagal neuroimmune axis modulates HF and is a promising target for treatment.
Keywords: Monocytes; monocyty; Humans; Mice; zvířata; alpha7 Nicotinic Acetylcholine Receptor; myši knockoutované; makrofágy; brain-heart axis; macrophages; alfa7 nikotinové acetylcholinové receptory; zánět; vagová stimulace; heart failure; TNF-alfa; mužské pohlaví; faktor 2 související s NF-E2; nervus vagus; Vagus Nerve; srdeční selhání; Optogenetics; Mice, Knockout; Tumor Necrosis Factor-alpha; myši; Inflammation; Animals; Macrophages; lidé; Mice, Inbred C57BL; optogenetika; Vagus Nerve Stimulation; Heart Failure; NF-E2-Related Factor 2; neuroimmune; Male; myši inbrední C57BL